Patterns of brain injury and outcome in term neonates presenting with postnatal collapse. Issue 3 (3rd November 2008) - Foran, A; Cinnante, C; Groves, A; Azzopardi, D V; Rutherford, M A; Cowan, F M
Abstract : Objective: To document perinatal events, brain imaging, neurophysiology and clinical outcome in term infants with early postnatal collapse (PNC). Design: Tertiary referral centre, retrospective case review (1993–2006). Patients: Infants born at ⩾36 weeks' gestation with early (<72 h) PNC. Peri-partum and post-collapse data were collated with clinical, electrophysiological, neuroimaging and autopsy data and neurodevelopmental outcome. Results: Twelve infants were studied; median gestation 39 weeks (36–41), birth weight 3150 g (1930–4010). Ten were born vaginally (including occipitoposterior (1), breech (2), water birth (2), ventouse/forceps (3)), and two by emergency caesarean section. Median Apgar scores were 9 (3–9) and 10 (8–10) at 1 and 5 min; median cord pH was 7.29 (7.18–7.34). All were thought to be well after birth. The median age at PNC was 75 min (10 min to 55 h). All infants required extensive resuscitation. The median pH after PNC was 6.75 (6.39–7.05). Seven infants became severely encephalopathic, with severely abnormal EEG/aEEG recorded within 12 h. MRI showed acute severe hypoxic–ischaemic injury. All died. One infant showed rapid recovery, had mild encephalopathy, and good outcome. Four infants had severe respiratory illness, normal background EEG, and MRI showing slight white matter change (n = 3) or a small infarction (n = 1). All had a good 2-year outcome. Conclusions: In this term cohort, early PNC was generally followed by severe encephalopathy, acute central grey matter injury and poor outcome, or severe respiratory illness, slight white matter change and good outcome. Early EEG and MRI predicted outcome accurately. However, no antepartum, intrapartum or other aetiological factors were identified. Further investigation is needed in larger PNC cohorts.